Study on changing arterial oxygen saturation level of athletes while performing a 21 days training course at an altitude of 2000 meters - Man, M. C.; Ganera, C. (Science, Movement & Health, 2016)
Aim. Among the scientific literature in sports training, introduction of training at altitude (2000m) in the preparation of biological competition is an acquisition as spectacular as it is efficient, disqualifying this way doping with blood (a risky method, that violates sporting ethics) and is credited with an increase of endurance of up to 7%. The research aims to carry out monitoring changes produced at the level of oxygen saturation in arterial blood (Sp O2), which leads to a significant increase in performance of the athletes, due to changes in physiological, biochemical, hematological, favorable performance products with body exposure hypoxia. Methods. The research was conducted on a group of 10 athletes during a training session of 21 days in the National Sports Complex in Piatra Arsa Bucegi, located at an altitude of 2000m. To conduct this research we used experimental methods, mathematical method Statico, graphical representation method. Results. Data analysis shows that during exposure the body to hypoxia, saturation, arterial oxygen decreases, which leads to the production in the body of physiological changes and biochemical growth-enhancing sports performance, and does not return to normal levels throughout the 21 days spent at altitude. Conclusions. Making one or more training sessions at altitude significantly improves the performance of runners by triggering physiological changes, hematological body athletes exposure to hypoxia, favorable growth performance.